MATHEMATICAL MODELING AND PREDICTION OF ONCHOCERCIASIS TRANSMISSION DYNAMICS TOWARD ELIMINATION IN TARABA STATE, NIGERIA - Torsen, Emmanuel; Usman, Danfulani Bitrus; Zemba, Ambrose Audu Zemba (FUDMA Journal of Sciences, 2025)
Onchocerciasis, commonly known as river blindness, is a neglected tropical disease caused by the filarial nematode Onchocerca volvulus and transmitted through bites of Simulium blackflies. A SEIR-SEI model was developed to simulate the bidirectional transmission dynamics between human and blackfly populations. The model incorporated key epidemiological parameters including transmission probabilities (human: 0.0005-0.001 per bite; vector: 0.001-0.0015 per bite), biting rate (0.3-0.7 bites/vector/day), incubation periods (human: 10-20 days; vector: 7-12 days), recovery rate (0.001-0.05 per day), and mortality rates (human: 0.000038 per day; vector: 0.05-0.1 per day). Seasonal variation was incorporated through sinusoidal functions with peaks at day 180. The basic reproduction number was calculated using the next-generation matrix approach. Results demonstrated that the calculated R₀ ranged seasonally from 0.004 to 0.013, with a baseline of 0.008 (R₀ < 1), indicating a projected gradual decline in transmission. The model predicted zero cases per 100,000 population by the fifth year, with disease prevalence stabilizing at very low levels as immunity accumulates. Seasonal oscillations were observed, with peak transmission occurring around day 180 (June-July), corresponding to periods of high vector abundance. The findings suggest that onchocerciasis in the studied LGAs of Taraba State is transitioning toward hypo-endemicity and eventual elimination. Targeted interventions, sustained vector control measures, scaled-up treatment programs, and continued epidemiological surveillance are recommended to accelerate disease elimination. These results align with Nigeria’s goal of eliminating onchocerciasis by 2030 and provide evidence-based guidance for targeted intervention strategies in endemic communities.